Clostridium difficile septic arthritis and periprosthetic joint infection in a patient with acute lymphoblastic leukaemia, T-/B-lymphocytopenia and hypogammaglobulinemia – a case report and review of the literature. Issue 5 (10th May 2021) - Karczewski, Daniel; Müllner, Maximilian; Perka, Carsten; Müller, Michael
Abstract : To the best of our knowledge, we report the first Clostridium difficile infection in a native hip joint with subsequent prosthetic joint infection in a patient at a state of hypogammaglobulinemia. The infection developed following chemotherapy for B-cell precursor acute lymphoblastic leukaemia (BCP-ALL). After chemotherapy, hip arthroplasty was performed for destructive septic arthritis. However, infection in the hip persisted with several failing revisions for more than 3 years, until ultimately hypogammaglobulinemia and T-/B-lymphocytopenia were diagnosed, and supplementation with i.v. immunoglobulins was able to achieve infection control.